Plastic matrix composites with continuous fiber reinforcement (Military handbook, 1991)
The properties of all basic plastics can be enhanced by the addition of fibers, whiskers, and particulate. Plastics so modified are referred to as organic or plastic matrix composites. The plastic matrix composites discussed in this handbook are restricted to those employing continuous fiber reinforcements. The fibers are fiberglass, carbon-graphite, aramid organic, and boron. Advantages in applications are discussed, and "pros and cons" are considered.